Estudo da toxicidade hepática da trans-desidrocrotonina (t-dctn), um diterpeno obtido de Croton Cajucara Benth, e de estratégias farmacológicas preventivas em modelos animais - Rabelo, Alana Fonteles Lima (2008)
The trans-dehydrocrotonin (t-DCTN) is a major diterpenoid compound present in bark extracts of Croton cajucara (Euphorbiaceae) stem. This diterpene possesses a wide spectrum of pharmacological activity that include anti-inflammatory, antinociceptive, hypoglycemic and antihyperlipidemic effects. Deleterious effects on liver are not uncommon with substances having this pharmacological profile. Keeping in view the reported hepatotoxicity of t-DCTN in vitro and in vivo, the present study was carried out to analyse in greater depth its potential to cause hepatic damage and then to seek pharmacological strategies to mitigate such a toxicity. Accordingly, our initial experiments were aimed to observe the hepatic damage in mice that received the single (acute) or repeated administrations of t-DCTN by oral gavage, at doses ranging from 10 to 300 mg/kg. The second series of experiments were designed to evaluate the effects of (i) pre-conditioning with a smaller dose t-DCTN or ethanol, and (ii) pre-treatments with Vitamin E or NAC on high-dose -associated hepatic injury in mice. A possible involvement of NO was also verified on the pre-conditioning effects of t-DCTN and or Ethanol. t-DCTN at higher doses (100 e 300 mg/kg, v.o.) caused severe hepatic damage as evidenced by significant (p<0,001) increases in the serum levels of ALT and AST and histopathological alterations, whether administered singly or repeatedly. In contrast, at the doses of 10 e 30 mg/kg, there were no significant alterations suggesting that the toxicity is a dose-related one. Pharmacological pre-conditioning with t-DCTN (10 mg/kg, p.o.) e Ethanol (1 g/kg, p.o.) significantly (p<0,001) attenuated the high-dose t-DCTN (100 mg/kg) -associated hepatotoxicity, as evidenced by reductions in serum enzyme activities as well as the hepatic lesions. In mice supplemented with L-arginine, the substrate for NO generation only partially prevented the hepatotoxic effect of t-DCTN most possibly due to an improved hepatic microcirculation. Additionally, pre-treatment with Vitamin E but not the NAC effectively reduced hepatotoxic effect of t-DCTN, evidenced by diminished serum levels of ALT, AST and hepatic TBARS and histological alterations. This suggests that Vitamine E protects against the increased hepatic lipid peroxidation promoted by high-dose t-DCTN. Paradoxically, compared to other hepatotoxicants reported in literature, t-DCTN enhanced the hepatic glutathione levels, which may be a consequence of prolonged oxidative stress. Taken together, these results confirm the earlier observations on the hepatotoxic potential of t-DCTN and suggest that an increased oxidative stress and lipid peroxidation of hepatocyte membranes contributes to hepatic damage. Supplementation with liposoluble antioxidant Vitamina E, or pré-conditioning with smaller doses of t-DCTN or ethanol might be useful prophylactically to overcome hepatotoxic effects of t-DCTN.